Sequential versus concomitant treatment of androgen receptor signaling inhibitors and docetaxel for metastatic hormone-sensitive prostate cancer: an network meta-analysis - Li, Chun Xing; Li, Cong Ying; Wang, Yu Qiao; Liu, Hua; Yang, Zhan Jiang; Zhang, Xian; Wang, Guan Chun; Wang, Lei (Frontiers in Pharmacology, 2024)
Background: Androgen receptor signaling inhibitors (ARSis), when administered sequentially or in combination with docetaxel and androgen deprivation therapy (ADT), have been shown to enhance overall survival (OS) and progression-free survival (PFS) in patients with metastatic hormone-sensitive prostate cancer (mHSPC). Nonetheless, the optimal sequence for administering chemotherapy and ARSis remains to be determined.Objective: To compare the efficacy of ARSis sequential therapy with ARSis combined therapy for mHSPC, and to evaluate the efficacy and safety of different combination regimens.The PubMed, Embase, Cochrane Central, and ClinicalTrials.gov databases were searched from their inception through July 14, 2024, to identify eligible phase III randomized clinical trials (RCTs) evaluating the combination or sequential use of docetaxel + ADT with abiraterone, enzalutamide, apalutamide, or darolutamide. The outcomes of interest included OS, PFS, time to prostate-specific antigen (PSA) progression, grade 3-5 adverse events (AEs), and serious adverse events (SAEs).Results: Five RCTs involving 2836 patients were included in the analysis. When comparing ARSis sequential therapy to ARSis combined therapy, no significant differences were observed in OS (Hazard Ratio (HR): 1.17, 95% Confidence Interval (CI): 0.69-1.96), PFS (HR: 1.03, 95% CI: 0.47-2.22), or time to PSA progression (HR: 0.48, 95% CI: 0.03-7.69). Within the different ARSis combined regimens, the triple therapies involving enzalutamide, abiraterone, and darolutamide demonstrated comparable efficacy and safety profiles in the overall population, and their efficacy in patients with high-volume disease or low-volume disease was also similar.ARSis sequential therapy did not significantly differ from ARSis combined therapy in improving OS and PFS among patients with mHSPC, and thus can be considered as a viable treatment option.